Porous Triple Network Hydrogel Humidity Sensor with Ultrafast Response for Wearable Health Monitoring - Shushu Chen; Tao Wang; Wenjin Luo; Yunzhen Zhang; Jie Jiang; Liang Chen (Chinese Physics B, 2026)
Abstract The rapid advancement of flexible and wearable electronics calls for humidity sensors that combine mechanical compliance with high sensitivity and fast response. However, conventional rigid-substrate sensors cannot conformally attach to soft surfaces and often suffer from signal instability under deformation. Here, we report a porous conductive triple network hydrogel humidity sensor designed through synergistic structural, electrical, and mechanical engineering. An interconnected microporous structure created by in situ CO 2 foaming accelerates water vapor transport. Carboxylated carbon nanotubes construct a uniform conductive network that enables efficient electrical signal transmission, whereas the triple-network matrix, integrated with covalent polyacrylamide crosslinks, sodium alginate–Ca 2+ ionic coordination, and tannic acid–Fe 3+ metal–phenolic interactions, effectively restrains volumetric swelling and imparts outstanding mechanical stability. The sensor achieves a wide RH sensing range (11.3%–97.3% RH), an ultrafast response/recovery time of ≤0.144 s, and stable operation over 300 cycles. It successfully distinguishes different breathing patterns and pathways in real time and enables non-contact finger proximity detection at millimeter distances. This work provides a rational design strategy for high speed wearable humidity sensors and intelligent non contact interfaces.